Impact of an Advanced Practice Pharmacist Type 2 Diabetes Management Program: A Pilot Study - Jelena Lewis; Tiffany Nguyen; Hana Althobaiti; Mona Alsheikh; Brad Borsari; Suzanne Cooper; David Kim; Enrique Seoane-Vazquez (University of Minnesota Libraries Publishing, 2019)
Background: The purpose of this study was to describe the impact of an Advanced Practice Pharmacist (APh) on lowering hemoglobin A1c (HbA1c) in patients with type 2 diabetes within a patient centered medical home (PCMH) and to classify the types of therapeutic decisions made by the APh. Methods: This was a retrospective study using data from electronic health records. The study evaluated a partnership between Chapman University School of Pharmacy and Providence St. Joseph Heritage Healthcare that provided diabetes management by an Advanced Practice Pharmacist in a PCMH under a collaborative practice agreement. Change in the HbA1c was the primary endpoint assessed in this study. The type of therapeutic decisions made by the APh were also evaluated. Descriptive analysis and Wilcoxon signed rank test were used to analyze data. Results: The study included 35 patients with diagnosis of type 2 diabetes mellitus managed by an APh from May 2017 to December 2017. Most of the patients were 60-79 years old (68.5%), 45.7% were female, and 45.7% were of Hispanic/Latino ethnicity. The average HbA1c was 8.8%±1.4% (range=6.0%-12.4%) and 7.5%±1.4% (range=5.5%-12.4%) at the initial and final APh visit, respectively (p<0.0001). Therapeutic decisions made by the APh included drug dose increase (35.5% of visits), drug added (16.4%), drug dose decrease (6.4%), drug switch (5.5%), and drug discontinuation (1.8%). Conclusion: The Advanced Practice Pharmacist's interventions had a significant positive impact on lowering HbA1c in patients with type 2 diabetes mellitus in a PCMH. The most common therapeutic decisions made by the APh included drug dose increase and adding a new drug.   Article Type: Pharmacy Practice